Perencanaan Pengembangan Alumni Perguruan Tinggi dalam Perspektif Islam - Handrianto, Budi; Rahayu, Anissa Maila; Mujahidin, Endin (Program Studi Magister Pendidikan Agama Islam, 2021)
The planning preparation of an activity is highly recommended in Islamic perspective. The completion of university's study program does not make the university complete its planning task. The existence of alumni as a necessity of the educational process has an important position and role in Islamic civilization and requires seriousness in planning its development. Currently, exploring concepts from an Islamic perspective is still limited, especially in terms of alumni development. The purpose of this study is to describe the concept of alumni in an Islamic perspective and to explain the planning of alumni development in the university. This study uses a qualitative approach with library research. The results of this study are (1) the term ‘alumni' in the Islamic perspective refers to a monumental event and (2) alumni development planning can use the POAC (planning, organizing, actuating, controlling) concept by George Robert Terry where the stages of the flow start from planning, then organizing, then mobilizing and finally monitoring. After knowing the role of alumni is very strategic, it is hoped that alumni development planning in the future will be managed properly and seriously.AbstrakPenyusunan suatu perencanaan kegiatan sangatlah dianjurkan dalam perspektif Islam. Selesainya program pendidikan tinggi tidaklah menjadikan perguruan tinggi tersebut selesai dalam tugas perencanaannya. Keberadaan alumni sebagai satu keniscayaan dari adanya proses pendidikan mempunyai posisi dan peran penting terhadap peradaban Islam dan perlu keseriusan dalam perencanaan pengembangannya. Saat ini, penggalian konsep dari perspektif Islam masih terbatas khususnya dalam hal pengembangan alumni. Tujuan penelitian ini adalah untuk mendeskripsikan konsep alumni dalam perspektif Islam dan menjelaskan perencanaan pengembangan alumni di perguruan tinggi. Penelitian ini menggunakan pendekatan kualitatif dengan kepustakaan. Hasil dari penelitian ini adalah (1) istilah ‘alumni' dalam perspektif Islam merujuk kepada kejadian yang monumental dan (2) perencanaan pengembangan alumni dapat menggunakan konsep POAC (planning, organizing, actuating, controlling) oleh George Robert Terry yang mana tahapan alurnya dimulai dari perencanaan, lalu pengorganisasian, kemudian penggerakan dan terakhir pengawasan. Setelah mengetahui peran alumni sangat strategis, maka diharapkan perencanaan pengembangan alumni kedepannya dikelola dengan baik dan serius.